Allocation of PV Systems from Residential Subareas to Distribution Transformers - Villavicencio, J. [UNESP]; Padilha-Feltrin, A. [UNESP]; Melo, J. D. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In order to develop studies such as the impact of residential photovoltaic (PV) system installation in low-voltage networks, the number of PV systems by transformer must be known. The number of residential PV systems can be estimated using socioeconomics information obtained in census data. This information is aggregated by census tract or subarea. In this paper, a technique to allocate estimated PV systems from the PV market potential in subareas to distribution transformers is presented. The proposed methodology is applied to a residential area in Brazil and, then, a voltage impact study in the low-voltage network is performed. The obtained results are hence useful on the planning and operation studies performed by utilities.
Keywords: Data disaggregation; low-voltage networks; photovoltaic system; voltage impact study